Analyses on the anthropocene from anthropology to philosophy - Yener, Bektas; Bektas, Oya Esra (Gyermeknevelés Tudományos Folyóirat, 2025)
Although there are differing views on when the Anthropocene began, the relationship between man and nature reached a critical point in history during this period. Since the beginning of the Neolithic period, the world’s population has grown significantly, reaching approximately eight billion people today, with more than half of them living in metropolitan areas. The growing population and density of cities have played a significant role in increased consumption of natural resources, the decline of biological diversity, and the emergence of ecological issues. Urbanisation has resulted in infrastructure and industrial activities that continue to disrupt the natural structure of the Earth. As a result, for the first time in history, the quantity of human-made objects has exceeded all living biomass. The apparent impact of humanity on the natural environment, which is viewed as the primary driving force behind these transitions, has raised concerns about the future. The solution to the growing concerns and escalating problems lies in reimagining and reconstructing the relationship between nature and man. In this regard, it is necessary to reconsider the definition of nature. What do we mean by nature? When asked this question, many people envision forests, mountains, or lakes. What is noteworthy, however, is that individuals do not place themselves within these images of nature. So, why does humanity position itself so distinctly apart from nature? To answer this, it is necessary to closely analyse the mode of modern thinking. The modern world’s way of thinking is based on a dualist perspective; everything is approached through opposites, and subject-object duality becomes more evident. Man has moved away from nature by confronting nature as an object and has begun to see himself as superior as a subject. Is this actually the case? In fact, each of us, like all life on earth, came from nature; we are its components.